IMPLEMENTASI PERATURAN MENTERI PERHUBUNGAN NOMOR PM 133 TAHUN 2015 TENTANG PENGUJIAN KENDARAAN BERMOTOR DALAM MEWUJUDKAN KESELAMATAN BERLALU LINTAS DI KUTAI KARTANEGARA - Sungudi, Abror; Noor, Muhammad; Utomo, Heryono Susilo (Jurnal Administrative Reform, 2022)
This study aims to analyze the implementation of the Regulation of the Minister of Transportation Number PM 135 of 2015 concerning Periodic Testing of Motorized Vehicles in Realizing Traffic Safety in Kutai Kartanegara Regency  focusing the research are: (1) Implementation of the policy of periodic testing of motorized vehicles which includes the sub focus of policy accuracy, accuracy of implementation, determination of targets and environmental accuracy, (2) the inhibit factors of successful implementation of the policy of Periodic Motor Vehicle Testing in Kutai Kartanegara. This research is a qualitative descriptive study. The results showed that the implementation of the motor vehicle testing policy in an effort to realize traffic safety in Kutai Kartanegara went well and contributed in reducing the number of traffic accidents. This can be seen from the four aspects of accuracy, namely policy accuracy, implementation accuracy, target accuracy and environmental accuracy which are also supported by policy support, strategic support, and technical support from related parts.